An in situ TEM nanoindentation-induced new nanostructure in cadmium zinc telluride. Issue 15 (6th April 2021) - Liu, Dongdong; Zhang, Zhenyu; Chen, Leilei; Wang, Dong; Cui, Junfeng; Chang, Keke; Guo, Dongming
Abstract : A new nanostructure induced by in situ TEM nanoindentation was observed, consisting of a single crystal, slip bands, stacking faults, a superlattice, a new tetragonal phase, and Moiré fringes. Abstract : Phase transformations occurring in a solid govern the structural and physical properties significantly. Nevertheless, deformation-induced phase transition in a soft-brittle solid has not been demonstrated yet. Soft-brittle cadmium zinc telluride (CZT) based instruments have produced technological breakthroughs in the semiconductor industry, and therefore their phase transformations have been widely investigated during the past 60 years. In this study, in situ transmission electron microscopy (TEM) nanoindentation was performed on CZT, and it was found that no brittle fracture occurred at a peak load of 41.9 μN, corresponding to a stress of 1.75 GPa. A new nanostructure induced by in situ TEM nanoindentation was observed, consisting of a single crystal, slip bands, stacking faults, a superlattice, a new tetragonal phase, and Moiré fringes. The new tetragonal phase was formed by partial Cd and Te atoms in the (111̄) plane slipping along the [1̄21̄] orientation, which was elucidated by ab initio simulations. It belongs to a tetragonal crystal system, and the lattice distances along the X and Y axes were 0.382 and 0.376 nm, respectively. Our findings provide new insights into the deformation-induced phase transformation for a soft-brittle solid, and have application potential in solar cells, radiation detectors, and medical imaging, quantum, flexible electronic and optoelectronic devices.